2007
DOI: 10.1016/j.jmhg.2007.06.003
|View full text |Cite
|
Sign up to set email alerts
|

High patient satisfaction amongst males participating in men's educational group appointments (MEGA) for routine physical exams

Abstract: Background: There is an insidious health crisis facing men in the United States today. They have a higher age-adjusted death rate, compared with that of women, from nearly all of the leading causes of death. Although genetics play a role, unhealthy behavior, avoidance of health care, and making poor healthrelated decisions also significantly contribute to premature death and disability amongst men. Having identified that behavior change amongst men is needed, and using the observation that group dynamics have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Conducting MEGA workshops in rural Nicaragua provided an environment in which men appeared to feel comfortable participating, in spite of belonging to a culture where machismo often precludes men from seeking health care. This finding was commensurate with some investigations in the United States ( Campbell et al, 2009 ; Campbell & Gosselin, 2007 ). During earlier visits to Nicaragua, it was observed that many men, who had made the journey with their families to the health post, not receive any care themselves.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Conducting MEGA workshops in rural Nicaragua provided an environment in which men appeared to feel comfortable participating, in spite of belonging to a culture where machismo often precludes men from seeking health care. This finding was commensurate with some investigations in the United States ( Campbell et al, 2009 ; Campbell & Gosselin, 2007 ). During earlier visits to Nicaragua, it was observed that many men, who had made the journey with their families to the health post, not receive any care themselves.…”
Section: Discussionsupporting
confidence: 93%
“…In the United States, gender-specific programs have been initiated which capitalize on the benefits of group dynamics, in efforts to educate men about preventive health ( Campbell & Gosselin, 2007 ). Such programs leverage the fact that group dynamics can be effective in behavior change programs, such as weight loss and abstinence from alcohol ( Hogan, Linden, & Najarian, 2002 ; Vederhus & Kristensen, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the topics covered were cancer screening (colon, prostate, and testicular), primary prevention of cardiovascular disease, prevention and treatment of metabolic syndrome, nutritional counseling, and the important role of exercise and mental health in good overall health and well-being. More extensive details regarding the sessions are given in our prior work (Campbell & Gosselin, 2007), with the additional option of influenza vaccination administration during flu season. At the conclusion of each session, patients were invited to complete a survey that addressed satisfaction with the experience and contained several questions designed to help the health care team understand the differences that patients perceived in the amount of relevant medical information they acquired during the MEGA, compared with what they would have expected from a traditional one-on-one visit (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…seeking routine primary care, which involves a group setting for the entire visit, with the exception of a private physical examination. The team identified that patient satisfaction was surprisingly high (Campbell & Gosselin, 2007) and discovered that patients frequently voiced that they were better educated about routine health issues after these sessions compared with their traditional one-on-one visits. This prompted further investigation of patients' perceptions of how much medical information they acquired in the Men's Educational Group Appointment (MEGA) compared with their level of learning during prior individual physical examinations.…”
Section: Success With Men's Educational Group Appointments (Mega): Subjective Improvements In Patient Educationmentioning
confidence: 99%